The Medici : portraits and politics, 1512-1570 - Christiansen, Keith; Falciani, Carlo; Bayer, Andrea; Cropper, Elizabeth, 1944-; Gasparotto, Davide; Hendler, Sefy, 1972-; Fenech Kroke, Antonella; Mozzati, Tommaso; Pilliod, Elizabeth; Siemon, Julia; Wolk-Simon, Linda; Metropolitan Museum of Art (New York, N.Y.) (New York, NY : The Metropolitan Museum of Art, 2021)
Between 1512 and 1570, Florence underwent dramatic political transformations. As citizens jockeyed for prominence, portraits became an essential means not only of recording likeness but also of conveying a sitter's character, social position, and cultural ambitions. This book explores the ways that painters, including Jacopo Pontormo, Agnolo Bronzino, and Francesco Salviati, sculptors such as Benvenuto Cellini, and others, endowed Florentine portraiture with the erudite and self-consciously stylish character that made it so distinctive. Although the Medici family had ruled Florence since 1434, Cosimo I de Medici, who became the second Duke of Florence in 1537, demonstrated a particularly shrewd use of culture as a political tool to transform Florence into a dynastic duchy and give Florentine art the central position it has held ever since. Featuring 100 paintings, sculptures, works on paper, and medals, this volume presents an exploration of a crucial and vibrant period in Italian art.
Power and identity in sixteenth-century Florentine portraiture / Carlo Falciani -- Vernacular identities: the Academia Fiorentina and the poetics of portraiture / Elizabeth Cropper -- Catalogue: From republic to Duchy, 1512-32 / Carlo Falciani -- Politics, portraiture, and the Medici Popes, 1513-34 / Linda Wolk-Simon -- Cosimo I de' Medici: lineage, family, and dynastic ambitions / Elizabeth Pilliod -- A poetics of portraiture and the legacy of Dante and Petrarch / Julia Siemon -- Cosimo and the politics of culture: reinventing Florence as a cultural capital / Sefy Hendler -- Redecorating the Palazzo Vecchio / Antonella Fenech Kroke -- Florence and Rome: Bronzino and Salviati / Carlo Falciani.
This catalogue is published in conjunction with "The Medici: Portraits and Politics, 1512-1570", on view at The Metropolitan Museum of Art, New York, New York, from June 26, 2021 through October 11, 2021--Colophon.
Includes bibliographical references (pages 297-318) and index.
Keywords: Medici, House of -- In motion pictures -- Exhibitions; Medici, House of -- Portraits; Portrait painting -- Exhibitions. -- Political aspects -- Italy; Portrait painting, Italian -- Exhibitions. -- 16th century; Portraits, Italian -- Exhibitions. -- 16th century; Nobility -- Portraits -- Italy